2014
DOI: 10.1159/000369930
|View full text |Cite
|
Sign up to set email alerts
|

Nox4 Is a Major Source of Superoxide Production in Human Brain Pericytes

Abstract: Background: Pericytes are multifunctional cells surrounding capillaries and postcapillary venules. In brain microvasculature, pericytes play a pivotal role under physiological and pathological conditions by producing reactive oxygen species (ROS). The aims of this study were to elucidate the source of ROS and its regulation in human brain pericytes. Methods: The expression of Nox enzymes in the cells was evaluated using RT-PCR and western blot. Superoxide production was determined by superoxide dismutase-inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 36 publications
1
48
0
Order By: Relevance
“…Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase subunit 4 (NOX4) is one of the proteins responsible for the ROS production in cerebral tissue [14]. The expression level of NOX4 in 10%O 2 was twice that in 21%O 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase subunit 4 (NOX4) is one of the proteins responsible for the ROS production in cerebral tissue [14]. The expression level of NOX4 in 10%O 2 was twice that in 21%O 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the mechanisms underlying the redox imbalance in hypoxic cerebral tissue, the mitochondrial complex I may be relevant [28], but NOX4, which nearly doubled from 21%O 2 to 10%O 2 , is likely a pivotal factor because it responds directly to hypoxia [29] and stands out as the main enzyme family that is dedicated to forming ROS [30], thereby constituting a major ROS source [14], [31]. On the other hand, Nrf2, one of the genes that are altered in rat brains after 12 h high altitude exposure [32], may represent a major mechanism that regulates antioxidant defenses [17].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that Nox4 expression increased in the diabetic ApoE −/− kidney in this study may seem contradictory. However, two reports claim that NOX4 contributes to the generation of superoxide under some disease conditions [34,35], highlighting the important nature of changes in ROS production between health and disease. H 2 O 2 levels were also observed to increase in the aorta after 30 mg kg −1 day −1 GKT137831 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nox proteins are well-established sources for ROS in various vascular diseases including brain injury [15, 16, 20, 37]. Several studies showed that enhanced Nox4 expression was accompanied with an increase not only in hydrogen peroxide but also superoxide [3842]. Nox4 silencing has been a promising strategy in improving neurovascular outcomes following I/R injury [21–23].…”
Section: Discussionmentioning
confidence: 99%